Kajian Literatur Tentang Implementasi Tujuan Pembangunan Berkelanjutan (SDGS) di Indonesia : Evaluasi dan Perspektif Berkelanjutan - Adila, Wafa; R, Refdi; Hadi, Fitra (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The achievement of the Sustainable Development Goals (SDGs) in Indonesia is a crucial issue involving various sectors, including the government, private sector, academia, and international organizations. Various reports, studies, and policies have documented the progress and challenges in SDG implementation, particularly in the context of digitalization, financing, and multi-stakeholder partnerships. Studies indicate that digital transformation plays a vital role in accelerating SDG achievement, while private sector funding is a key factor in program sustainability. Additionally, there are disparities in achievement between regions, necessitating more inclusive policy approaches. Indonesia has achieved 62.5% of its 2030 SDG targets, the highest in Asia, although its regional ranking remains fluctuating. Several studies also highlight climate change as a major challenge in SDG attainment. Systematic reviews show that network-based approaches and policy analysis are effective methods for assessing SDG implementation efficiency. Furthermore, academic engagement in public policy studies and systematic analysis is integral to identifying strategies for accelerating SDGs in Indonesia. Therefore, continuous synergy between the government, private sector, academia, and society is essential in overcoming obstacles and accelerating SDG achievement in Indonesia.